The need for early-stage safety assessment in the development of nanomaterials – the role of nanotoxicology - Louro, Henriqueta (2021)
The exponential growth of technology based on nanomaterials(NMs), due to their perspectives and application in key sectors such as agriculture, food industry, medicine, energy, environment, and electronics, has led to their increased use. Many products, already available, have NMs, such as silver or titanium dioxide nanomaterials and others are being developed, such as nanocelluloses and nanoformulations of pesticides. However, the NMs’ specific physicochemical properties that confer them beneficial unique characteristics can also elicit nano-bio interactions leading to toxic potential and concerns for public health. Furthermore, their properties can be affected by the surrounding matrix, leading to secondary features potentially more relevant then primary characteristics for determining the toxicological outcome. Processes like intake or digestion may modify the NMs characteristics leading to unexpected toxicity in human cells. Due to these uncertainties, the investigation of the genotoxic properties of NMs that may imply cancer onset has been mostly inconclusive. Therefore, to contribute for the safety assessment of NMs, it is important to try to ascertain the NM characteristics, primary or secondary, that determine the adverse effects, allowing the synthesis of innovative NMs devoid of toxicity. Here, the nanotoxicology approaches to the hazard assessment of titanium dioxide nanomaterials and nanocelluloses is presented. It is precluded that incorporating adequate nanosafety assessment early in the development of new NMs, will lead to a “safe-by-design” approach that will enable safety to keep pace with innovation.